Freirean Literacy Approach: A Functional Model to the Solution of the Problems of Unemployment and Poverty amongst Nigerian Youth - Obidiegwu, U. J.; Oronsaye, Osayemwenre Rita (NIU Journal of Humanities; Vol 11 No 1 (2026): NIU Journal of Humanities, Vol. 11 No. 1, March 2026DO - 10.58709/niujhu.v11i1.2457, 2026)
The overall goal of this study was to propose Freirean literacy approach as a functional model to the solution of the problems of unemployment and poverty amongst Nigerian youths.  Unemployment is seen as a situation in which persons capable and willing to work are unable to find suitable paid employment. Youth unemployment and poverty rate is high in Nigeria and has been seen to take an increasing turn, over the years. The paper sought to propose sustainable solution to poverty and unemployment which is ravaging Nigerian youths by embarking on analytical review and report of the Freirean Literacy Approach. The paper discussed poverty and employment, consequences of unemployment and poverty, government poverty alleviation and unemployment programme, principles of Freirean functional literacy approach, Freire literacy approach and application to the solution of unemployment and poverty in Nigeria. It was concluded that, Freirean literacy approach should be tried out in Nigeria for the solution of poverty and unemployment challenges that bedevils the country for sustainable growth and development, hence, it has been tried out and was successful in some other countries. It was therefore recommended that a well-funded functional literacy and skill acquisition programme using REFLECT approach should be established by government in all communities in Nigeria. Keywords: Freirean Literacy Approach, Unemployment, Youth Unemployment, Poverty, Nigeria, Education